Long weekly working hours and ischaemic heart disease: a follow-up study among 145 861 randomly selected workers in Denmark. Issue 6 (15th June 2018) - Hannerz, Harald; Larsen, Ann Dyreborg; Garde, Anne Helene
Abstract : Objectives: The aim of the present study was to test if incidences of ischaemic heart disease (IHD) and usage of antihypertensive drugs are independent of weekly working hours (WWH) among full-time employees in Denmark. Design and participants: Data on WWH from participants of the Danish labour force surveys, 1999–2013, were linked on an individual level to national registers with data on socioeconomic status (SES), industry, emigrations, redeemed prescriptions, hospital contacts and deaths. Participants were followed until the end of 2014 (on average 7.7 years). Poisson regression was used to model incidence rates as a function of WWH. The analyses were controlled for calendar time, time passed since start of follow-up, employment in the healthcare industry, age, sex, SES and night work. Results: In total, we found 3635 cases of IHD and 20 648 cases of antihypertensive drug usage. The rate ratio of IHD was 0.95 (95% CI 0.85 to 1.06) for 41–48 compared with 32–40 WWH and 1.07 (0.94 to 1.21) for >48 compared with 32–40 WWH. The corresponding rate ratios for antihypertensive drug usage were 0.99 (0.95 to 1.04) and 1.02 (0.97 to 1.08). No statistically significant interactions between WWH and sex, SES and night work, respectively, were found. Conclusion: In this Danish sample, we did not find any statistically significant association between WWH and IHD or antihypertensive drug usage.